The effect of ionizing radiation from dental radiographic devices on dental pulp stem cells - Kahraman, Onur Evren; Karaman, Tahir; Yildirim, Tuba Talo; Etem, Ebru; Dündar, Serkan; Tektemur, Ahmet (My University, 2023)
Aim: This study aims to investigate the effects of exposure to different doses delivered by radiographic diagnostic tools on cell death pathways in isolated dental pulp stem cells on a molecular level using qRT-PCR data. Methodology: Seventy fully impacted mandibular third molars were used for the study. Extracted third molars were divided into seven groups (n = 10 each): A control group receiving no radiation, periapical (PER), panoramic (PAN), and dental tomography (CBCT) groups receiving one dose of radiation each, and periapical, panoramic, and CBCT groups receiving three consecutive doses of radiation each. Then, gene expressions in dental pulp stem cells were evaluated using the qRT-PCR this method. Results: A significant difference was found in the expression of the ULK1 gene in the dental pulp tissue samples from the PAN1 group; GABARAP, LAMP3, APAF1, BCL2, CASPASE2, and CASPASE7 genes from the PER1 group; the ULK1 gene from the PER3 group; and ATG12, ATG16L1, ATG4A ATG5, BECN1L1, GABARAP, LAMP1, LAMP3, MAP1LC3B, ULK1, APAF1, BCL2, CASPASE-2, CASPASE-3, CASPASE-7, and CASPASE-8 genes from the CBCT3 group. Conclusion: While the radiation doses we applied to the DPSC cell culture are considered low levels, there was an increase in cell death markers with increased exposure to radiation through multiple radiography procedures. Taking measures to prevent errors during radiography and avoiding repeated, unnecessary patient exposure to radiation would help minimize the damaging effects of radiation.
Keywords: QRT-PCR; radiography; cell culture; ionizing radiation; mRNA expression; Dental pulp stem cells